Critical appraisal of an irrigation command and water productivity based on satellite remote sensing (International Journal of Irrigation and Water Management, 2018)
Irrigation policy makers and managers need information on the irrigation performance and productivity of water at various scales to devise appropriate water management strategies, considering dwindling water availability, further threats due to continually rising population and food demand. It is often difficult to access sufficient water supply and use data to determine crop water consumption and irrigation performance. Energy balance techniques using remote sensing data have been developed by various researchers, and can be used as a tool to directly estimate actual evapotranspiration that is, water consumption. Study demonstrates how remote sensing-based estimates of water consumption and water stress combined with secondary agricultural production data, which provide better estimates of irrigation performance, water productivity. A principle benefit of the approach is that it allows identification of areas where agricultural performance is less than potential, there by providing insights into how irrigation systems can be managed to improve overall performance and increase water productivity in a sustainable manner. To demonstrate the advantages, the approach is planned to be applied in North Gujarat, India based Dharoi Irrigation Scheme. Remote sensing-based indicators reflecting equity, adequacy, reliability and water productivity can be estimated. This paper is purely the extensive research review and conceptualized concept to be used for future research in above said region.